Circular Economy and Sustainable Reengineering: Curricular Applications in Engineering Education at UNEXPO-VRB (Gestión y Gerencia, 2025)
The circular economy has become a key curricular approach to sustainability, promoting resource optimization and waste reduction in engineering education. In the Venezuelan university context, the application of sustainable reengineering strategies allows for the transformation of educational and administrative processes toward more efficient, ethical, and environmentally responsible models, favoring the reuse of resources and the management of pedagogical practices aligned with quality and sustainability standards. This article analyzes recent trends (2020–2025) in the circular economy and its impact on engineering education at the National Experimental Polytechnic University “Antonio José de Sucre” (UNEXPO), Barquisimeto Vice-Rectorate (VRB), based on a literature review of six articles selected for their theoretical, educational, and contextual relevance. From a qualitative perspective, a heuristic process was developed under the interpretive paradigm and the hermeneutic method, aimed at understanding how these trends can be contextualized within Venezuelan higher education. The study phases included: information gathering, critical understanding, theoretical discussion, and reflective synthesis. The theoretical integration technique using matrices was applied to organize the findings and reveal significant contributions. Although most of the analyzed articles originate from Latin America, a European reference is included due to its methodological value in the evaluation of academic projects. Finally, it is understood that the circular economy and reengineering contribute to the development of key professional competencies, such as critical thinking, collaborative work, systemic anticipation, and ethical problem-solving, fostering curricular transformation toward regenerative, contextualized models committed to the environment, in order to build a more just future through sustainable design.
Keywords: Curriculum; higher education; circular economy; reengineering and sustainability